Kepemimpinan Kiai dalam Menanamkan Nilai-Nilai Moderasi Beragama di Pondok Pesantren At Tahdzib Rejoagung Ngoro Jombang - Sutrisno, Sutrisno; Fahmi, Moh. Ifan (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
The emergence of the term religious moderation in Indonesia in recent times is closely related to various phenomena of intolerance, radicalism, and terrorism that occur in Indonesia. Moderation is a life view that always prioritizes the attitude of tolerance and always takes the middle road from two opposing attitudes. Islamic boarding schools are an integral part of the institutions that exist in Indonesia which instill religious values and practices in their students for the advancement of national development. As a subculture rooted in Islamic culture in Indonesia, Education in boarding schools, not only provides educational facilities and practices, but also instills a number of values or norms. One of them is the Islamic boarding school At-Tahdzib Rejoagung in Ngoro district. The Islamic boarding school At-Tahdzib as an educational institution has proven to be quite excellent in producing generations of the nation who have good character. One of the proofs is the large number of alumni of At-Tahdzib pesantren who are trusted by the community to become educators in various formal and non-formal educational institutions. This is certainly inseparable from the role of kiai leadership who are also teachers in the educational process. The role of leadership is an attitude and behavior in influencing human resources, so that they are willing to carry out their duties to achieve organizational goals effectively and efficiently. This study aims to examine the leadership of kiai in instilling the values of religious moderation in Islamic boarding schools. More specifically, this article intends to identify strategies and analyze the influence of kiai leadership in instilling the values of religious moderation at the Islamic boarding school At Tahdzib Ngoro Jombang